The mountain [videorecording (DVD)] - Alverson, Rick, 1971-; Alverson, Rick, 1971-; Sheridan, Tye, 1996-; Goldblum, Jeff, 1952-; Gross, Hannah, 1990- (Kino Lorber, 2019)
After the death of his father, a shy young man, whose mother was lobotomized before her presumed death, meets by chance and starts working with a doctor performing frontal lobotomy procedures, traveling with him from asylum to asylum and documenting his work.